PENGURANGAN FFA DAN WARNA DARI MINYAK JELANTAH DENGAN ADSORBEN SERABUT KELAPA DAN JERAMI - Julius Fernando Pakpahan; Tomas Tambunan; Agnes Harimby; M. Yusuf Ritonga (Talenta Publisher (Universitas Sumatera Utara), 2013)
Jelantah is a cooking oil that has been used in a few time. It is not only have an unattractive colour and rancid, but also can make a risk to the health. Jelantah can be recovered by adsorbing the impurities and reduce color using the adsorbents. This study aimed to reduce levels of FFA and color of jelantah using coconut fiber and straw adsorbents with variation 50,70 and 100 mesh, variations in pressure at 1 atm and below, and the time variation of adsorption every 10 minutes during the first half hours. In this study, the best adsorbent to reduce free fatty acid (FFA) is coconut fiber with a pressure below 1 atm where FFA value before adsorbed is 0.006823 N and after being adsorbed 0.0002924 N, whereas for the reduction of oil color, the best adsorbent is straw with 100 mesh size because it reduces the color of 5.5 red and 24 yellow to 3.3 red and 21 yellow.